2022
DOI: 10.32604/jrm.2022.016260
|View full text |Cite
|
Sign up to set email alerts
|

Intratree Variation in Viscoelastic Properties of Cell Walls of Masson Pine (Pinus Massoniana Lamb)

Abstract: In this study, Pinus massoniana Lamb at different heights, across the annual rings, and between earlywood and latewood was measured by X-ray diffraction and the chemical composition was analyzed by chemical treatment. Results indicated that the microfibril angle (MFA) decreased and the chemical composition changed little with the increase in height from 1 m to 9 m. In the radial direction, the MFA decreased and the chemical composition changed little with an increase in annual rings. The cellulose content of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Masson pine is an economically important industrial timber tree that is widely distributed in China. Compared with other timber trees, the relative cellulose content, average elastic modulus, and hardness of Masson pine wood were larger [20], and it has always been considered an important wood resource for the fiber (for pulp, paper products, and boards) and sawn timber (for building houses and furniture) industries in China [21]. Therefore, understanding the genetic regulation of SCW formation in Masson pine could inform TF modification strategies to improve the sustainable production of wood fiber and lumber.…”
Section: Introductionmentioning
confidence: 80%
“…Masson pine is an economically important industrial timber tree that is widely distributed in China. Compared with other timber trees, the relative cellulose content, average elastic modulus, and hardness of Masson pine wood were larger [20], and it has always been considered an important wood resource for the fiber (for pulp, paper products, and boards) and sawn timber (for building houses and furniture) industries in China [21]. Therefore, understanding the genetic regulation of SCW formation in Masson pine could inform TF modification strategies to improve the sustainable production of wood fiber and lumber.…”
Section: Introductionmentioning
confidence: 80%
“…The survival rate of termites fed an ML diet in this study was slightly higher than previously reported rates associated with a rice straw diet and lower than rates associated with diets consisting of corn stover or soybean residue, although the dietary intake was higher than for these grass-based diets. Relative to pinewood, M. micrantha leaves contain less cellulose (ML: 21.31%, PW: 43.12-49.25%) and lignin (ML: 20.67%, PW: 26.12-35.42%) content [25,36], potentially leading to the increased ML dietary intake by these termites such that they were able to sustain themselves on this diet. However, this increase in overall dietary intake by termites fed an ML diet may have also resulted in the increased intake of toxic secondary plant substances [37], resulting in adverse survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be related to the quantity of lignin in the wood cell walls, which was the determining factor for the thermal softening properties of water-swollen wood [29]. Compared to LW with a lignin content of 28.31%, EW had a higher lignin content of 33.88% [30]. Consequently, the tensile modulus for EW was more sensitive to temperature changes compared to LW.…”
Section: Microfibril Angle (Mfa)mentioning
confidence: 99%